Research Progress of Tooth Surface Friction Force Gear Transmission - Xuefei Li; Jiqiang Li; Zhuo Chen; Zhiyuan Li; Lubing Shi; Zhongming Liu (Jixie chuandong)
Tooth surface friction has an important impact on the scoring，macro and micro pitting corrosion and transmission efficiency of meshing gear pairs. The research on the calculation and control method of tooth surface friction has significant engineering significance for the performance optimization and efficiency improvement of meshing gear pairs. It is precisely based on the important role of tooth surface friction that many scholars at home and abroad have conducted comprehensive studies on the calculation of friction coefficient and the influence of tooth surface friction on the contact damage and dynamic characteristics of meshing gear pairs. However，there is still no unified calculation method and design specification，there are still many technical research deficiencies，and it is still difficult to obtain reliable application in engineering. By summarizing relevant technical literatures at home and abroad，the current research status of tooth surface friction is expounded，the difficulties and hotspots in the research are sorted out， the development trend of tooth surface friction is predicted， and reference technical direction for further research on tooth surface friction is provided.